Correlações canônicas entre caracteres fenológicos, morfológicos, produtivos e nutricionais de genótipos de milho - Alves, Bruna Mendonça (2015)
The aim of this study was to identify through canonical correlation analysis if there is linear dependence among the phenological, morphological, and productive traits with protein-nutritional and energetic-nutritional traits in early maturing, super-early maturing, and transgenic maize genotypes. Three experiments were carried out in the agricultural year of 2009/2010 at the experimental area of the Plant Science department, in the Federal University of Santa Maria. The experiments were designed utilizing the randomized block design with three repetitions. In total, 76 maize genotypes were evaluated (36 early maturing, 22 super-early maturing, and 18 transgenic genotypes). The following traits were measured in each canonical group: phenological - number of days from sowing until male flowering and number of days from sowing until female flowering; morphological - plant height at harvest, ear insertion height at harvest, and relative ear placement; productive - number of plants, number of ears, ear index, ear weight, grain yield, and thousand grains weight; protein-nutritional - crude protein, lysine, methionine, cysteine, threonine, tryptophan, valine, isoleucine, leucine, phenylalanine, histidine and arginine; and energetic-nutritional - apparent metabolizable energy corrected for nitrogen, ether extract, starch, and amylose. The variance analysis was performed for each trait. It was determined the matrix of phenotypic correlation coefficients among the traits and the multicollinearity diagnosis was conducted within each group of traits. Posteriorly, it was held canonical correlation analysis for the early maturing, super-early maturing, and transgenic maize genotypes, within the following groups: phenological and protein-nutritional, morphological and protein-nutritional, productive and protein-nutritional, phenological and energetic-nutritional, morphological and energetic-nutritional, and productive and energetic-nutritional. In super-early maturing genotypes, the significant canonical correlation between phenological and protein-nutritional traits and between productive and protein-nutritional traits indicates linear dependence. In early maturing genotypes, there is linear dependence between phenological and energetic-nutritional traits. Furthermore, in super-early maturing genotypes, the significant canonical correlation between phenological, morphological, and productive traits and energetic-nutritional traits indicates linear dependence. Moreover, there is linear dependence between phenological and energetic-nutritional traits in transgenic genotypes.